Teaching Digital Pragmatics: Politeness Strategies and Face Negotiation in Real-Time Game-Based Interaction - Agustina, Ika; Sinaga, Rommel; Ginting, Pirman (Universitas Lancang Kuning, 2025)
In the context of increasingly dynamic digital communication, multiplayer online games have evolved into socially rich environments where real-time interaction reflects complex pragmatic behavior. This study investigates how players from Southeast Asian gaming communities negotiate face and utilize politeness strategies during live voice-based gameplay. Unlike previous research that centers on text-based or asynchronous interactions, this study addresses a critical gap by examining how paralinguistic elements such as tone, laughter, and vocal exaggeration influence pragmatic choices in synchronous digital communication. Grounded in Brown and Levinson’s Politeness Theory and Goffman’s concept of face, the study analyzes 120 naturalistic voice chat interactions collected from Overwatch 2 and Dota 2 using qualitative discourse analysis and thematic coding. The results demonstrate that players frequently rely on humor, indirect expressions, and culturally rooted metaphors to manage face-threatening acts and sustain group cohesion under competitive pressure. Rather than confronting errors directly, players use strategic tone modulation to reframe criticism as shared amusement, thus preserving social harmony. The study contributes to digital pragmatics by emphasizing the performative and relational aspects of game-based interaction. These findings carry broader implications for understanding emotional regulation, intercultural communication practices, and the development of socially aware interaction systems in online platforms that prioritize rapid, collaborative exchanges.